PENGARUH LATIHAN ABDOMINAL STRETCHING TERHADAP INTENSITAS DISMENORE - Syafna, Annisa; Dewi, Yulia Irvani; Hairani Damanik, Siti Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Dysmenorrhea is one of the most common gynecological problems experienced during adolescence, is very disturbing activities and often require the patient to rest and leave the activity. This study was aimed to determine the influence of abdominal stretching exercise against intensity of dysmenorrhoe. The design of this research study was "Quasy experiment" using the draft "Non-equivalent control group" which is divided into an experimental group and a control group. The study was conducted on student Pondok Pesantren Daarun Nahdhah. Total sample was 34 female students who fit the inclusion criteria and using simple purposive sampling technique. Measuring instruments are used sheets observasi numeric rating scale. The analysis used univariate and bivariate analysis using independent sample T-test and dependent sample t test. The results was showed a decrease in the intensity of dysmenorrhoe in the experimental group after given abdominal stretching exercise with p value (0.000) <α (0.05). This means that abdominal stretching exercise was effective to reduce the intensity of dysmenorrhoe. Abdominal stretching exercise can reduce dysmenorrhe in non-pharmacological which can be practiced independently, so it was suggested to students who have other family members or neighbors can use complementary therapies to reduce pain intensity of dysmenorrhoe. Key words: abdominal stretching exercise, dysmenorrhoe